Demorest's Family Magazine - Demorest, William Jennings (New York : W. J. Demorest., 1891)
A Happy Day at Cairo -- Summer's Bird: The Swallow -- The Last Cruise of the Galatée. -- Women and Baseball. -- The River of Pearls. -- Signs of Character in the Face: How to Read Them -- The Game of Lawn Crooketta. -- John's Suggestion. -- Miss Jo -- Our Girls: Nannie's Picnic -- Sanitarian: The Care of the Eyes. -- Home Art and Home Comfort: China Painting for Beginners; Cover for Tennis Racket. -- Kindergarten Work and Play for the Home: Slats and Sticks -- What Women are Doing. -- The World's Progress. -- Artistic Notes. -- Chat. -- Household: Keeping Rooms Cool -- Fruits for Breakfast. -- Mirror of Fashions: Review of Fashions - August -- Descriptions of Our Cut Paper Patterns. -- Supplement to Demorest's Family Magazine for August, 1891. -- Protection and Security Dependent on Liberty and Law. -- Extracts From the Speech of Hon. Joseph D- Taylor, March 3, 1891 -- Alcoholic Poisoning -- Anti-Nuisance League. -- Household. -- Prohibition
Demorest's New York Illustrated News Mme.; Demorest's Quarterly Mirror of Fashions
Digitized from original print, Valdosta State University Archives and Special Collections, 06-2016
Keywords: Women’s History; Fashion; Periodicals; Dress Making < Periodicals; Magazines